Anode for lithium secondary battery and lithium secondary battery including the same

KR103011834B1Active Publication Date: 2026-09-01SK ON CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020250091580
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-07-08
Publication Date
2026-09-01
Estimated Expiration
2042-10-21

Smart Images

  • Figure 112025076889111-PAT00002_ABST
    Figure 112025076889111-PAT00002_ABST
Patent Text Reader

Abstract

The negative electrode for a lithium secondary battery according to the present invention comprises: a negative electrode current collector; a first negative electrode composite layer formed on at least one surface of the negative electrode current collector and comprising a silicon-based active material including a Si-C composite, a first carbon-based active material, a conductive material, and a binder; and a magnesium-doped SiOx(0) formed on the first negative electrode composite layer. <x<2) 실리콘계 활물질,제2 탄소계 활물질, 도전재 및 바인더를 포함하는 제2 음극 합제층을 포함함으로써 음극의 부피 팽창을 완화하면서 고용량, 고에너지밀도 설계구현이 가능하며, 동시에 급속 충전 성능이 향상된 리튬 이차 전지용 음극 및 이를 포함하는 리튬 이차 전지를 제공할 수 있다.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a negative electrode for a lithium secondary battery and a lithium secondary battery including the same, and more specifically, to a negative electrode for a high-capacity secondary battery having a multilayer structure and excellent rapid charging characteristics, and a lithium secondary battery including the same. Background Technology

[0002] Recently, extensive research has been conducted on electric vehicles (EVs) to replace fossil fuel-powered vehicles, such as gasoline and diesel cars, which are major causes of air pollution. Lithium-ion batteries, which offer high discharge voltage and output stability, are primarily used as the power source for these EVs. Consequently, the need for lithium-ion batteries with high energy density is increasing, and active development and research are also underway regarding high-capacity anodes to meet this demand.

[0003] To realize high-capacity and high-energy-density secondary batteries, active development is underway to apply silicon-based active materials, which have a higher discharge capacity than graphite, to the negative electrodes of secondary batteries. When silicon-based active materials with such high discharge capacity are applied together with carbon-based active materials such as graphite, the loading weight (LW) of the negative electrode composite layer can also be reduced, thereby further increasing energy density.

[0004] However, silicon-based active materials exhibit a slower lithium ion diffusion rate and a higher volume expansion rate compared to carbon-based active materials, making it difficult to secure excellent rapid charging and lifespan characteristics for anodes containing silicon-based active materials. Accordingly, there is a need for the development of anodes for secondary batteries that possess excellent capacity, rapid charging, and lifespan characteristics.

[0005] For example, Korean Patent No. 10-1057162 discloses a metal-carbon composite cathode active material for improving cycle characteristics. The problem to be solved

[0006] The present invention aims to provide a cathode having high capacity and high energy density while mitigating volume expansion of the cathode.

[0007] In addition, the present invention aims to provide a negative electrode for a lithium secondary battery with improved rapid charging performance as another embodiment.

[0008] Furthermore, the present invention aims to provide a lithium secondary battery comprising a negative electrode as described above. means of solving the problem

[0009] A negative electrode for a lithium secondary battery according to one embodiment of the present invention comprises: a negative electrode current collector; a first negative electrode composite layer formed on at least one surface of the negative electrode current collector and comprising a silicon-based active material including a Si-C composite, a first carbon-based active material, a conductive material, and a binder; and a magnesium-doped SiOx(0) formed on the first negative electrode composite layer. <x<2) 실리콘계 활물질,제2 탄소계 활물질, 도전재 및 바인더를 포함하는 제2 음극 합제층을 포함한다.

[0010] The above Si-C composite may include carbon-based particles containing pores and a silicon-containing coating formed inside the pores of the carbon-based particles or on the surface of the carbon-based particles.

[0011] The binders of the first cathode composite layer and the second cathode composite layer may include rubber-based binders and cellulose-based binders.

[0012] The conductive materials of the first cathode composite layer and the second cathode composite layer may include one or more selected from the group consisting of carbon nanotubes (CNT) and graphite.

[0013] The first carbon-based active material and the second carbon-based active material may independently be one or more selected from the group consisting of natural graphite, artificial graphite, graphitized carbon fiber, graphitized mesocarbon microbeads, and amorphous carbon.

[0014] The weight ratio of the silicon-based active material and the first carbon-based active material included in the first cathode composite layer may be 1:5 to 20.

[0015] The weight ratio of the silicon-based active material and the second carbon-based active material included in the second cathode composite layer may be 1:4 to 16.

[0016] The thickness ratio of the first cathode composite layer and the second cathode composite layer may be 1:1 to 1.25.

[0017] At least one of the silicon-based active material of the first cathode composite layer and the silicon-based active material of the second cathode composite layer may have a carbon coating layer disposed on the outermost portion.

[0018] A lithium secondary battery according to another embodiment of the present invention comprises the negative electrode; and a positive electrode positioned opposite to the negative electrode. Effects of the invention

[0019] According to the present invention, it is possible to implement a high-capacity, high-energy-density design while mitigating volume expansion of the negative electrode, and at the same time, provide a negative electrode for a lithium secondary battery with improved rapid charging performance and a lithium secondary battery including the same. Brief explanation of the drawing

[0020] FIG. 1 is a schematic cross-sectional view showing the structure of a negative electrode for a secondary battery according to one embodiment of the present invention. Figure 2 is a graph showing the rapid charging life characteristics according to the type of silicon-based active material. Figure 3 is a graph showing the general (room temperature) lifespan characteristics according to the type of silicon-based active material. Specific details for implementing the invention

[0021] Preferred embodiments of the present invention are described below. However, embodiments of the present invention may be modified in various other forms, and the scope of the present invention is not limited to the embodiments described below.

[0022] Additionally, in this specification, singular expressions include plural expressions unless the context clearly indicates otherwise, and throughout the specification, the same reference numerals or reference numerals assigned in a similar manner refer to the same component or corresponding component.

[0023] Generally, as a method to improve the rapid charging characteristics of a lithium secondary battery, the loading amount of the negative electrode active material or the rolling density of the negative electrode is reduced, and the porosity of the negative electrode is increased to facilitate the movement of ions and / or electrons, thereby enabling charging at a high charging speed.

[0024] However, as described above, if the loading amount or rolling density decreases, it becomes difficult to increase the density of the cathode, making it difficult to obtain a high-capacity battery, and the adhesion between the cathode composite layer and the cathode current collector decreases, which may lead to a deterioration in lifespan characteristics.

[0025] In addition, as mentioned above, silicon-based active materials included to increase the capacity of the negative electrode for secondary batteries generally have a slower lithium ion diffusion rate compared to carbon-based active materials, so rapid charging characteristics may be relatively lacking.

[0026] Accordingly, the inventors of the present invention have confirmed that the above-mentioned problems can be substantially resolved by applying different silicon-based active materials to each layer of a 'multilayer structure' cathode. With reference to FIG. 1, embodiments of the present invention will be described in detail below.

[0027] FIG. 1 is a schematic cross-sectional view showing the structure of a negative electrode for a secondary battery according to one embodiment of the present invention.

[0028] A negative electrode (100) for a lithium secondary battery according to one embodiment of the present invention includes a negative electrode current collector (10) and a negative electrode composite layer (20) formed on the negative electrode current collector (10).

[0029] The above negative current collector (10) may include a metal that has high conductivity, improved adhesion to the negative slurry, and is non-reactive in the voltage range of the secondary battery. For example, the negative current collector (10) may include copper, stainless steel, nickel, titanium, or an alloy thereof. The negative current collector (125) may include copper or stainless steel surface-treated with carbon, nickel, titanium, or silver.

[0030] A negative electrode composite layer (20) comprising a silicon-based active material and a carbon-based active material is formed on at least one surface of the negative electrode current collector (10). The negative electrode composite layer (20) may be coated on the upper surface and the lower surface of the negative electrode current collector (10), respectively. The negative electrode composite layer (20) may come into direct contact with the surface of the negative electrode current collector (10).

[0031] According to one embodiment of the present invention, the cathode composite layer (20) with respect to one side of the cathode current collector has a multilayer structure comprising a first cathode composite layer (21) formed on the side of the cathode current collector (10) and a second cathode composite layer (22) formed on the surface side, wherein the first cathode composite layer (21) may be formed directly on the surface of the cathode current collector (10) and the second cathode composite layer (22) may be formed directly on the surface of the first cathode composite layer (21).

[0032] The first cathode composite layer (21) and the second cathode composite layer (22) each include a carbon-based active material and a silicon-based active material, but the first cathode composite layer and the second cathode composite layer each include an independent silicon-based cathode active material.

[0033] The silicon-based active material of the first cathode composite layer (21) of the present invention is a silicon-based active material comprising a porous structure, and specifically, may include a silicon carbide-based active material such as a Si-C composite, which is a compound represented by the chemical formula SiC. The porous structure is a structure comprising carbon-based particles containing pores and a silicon-containing coating formed inside the pores of the carbon-based particles and / or on the surface of the carbon-based particles.

[0034] The above Si-C composite has high capacity and low resistance characteristics compared to conventional silicon oxide-based active materials. In addition, since silicon is present within the structure of the above Si-C composite, which is similar to graphite, it can mitigate the phenomenon of electrode cracking caused by volume expansion of the active material containing silicon-based oxide and can ensure conductivity. By applying the first negative electrode composite layer (21) containing the above Si-C composite to the lower layer, the resistance occurring between the negative electrode current collector (10) and the negative electrode composite layer (20) can be minimized, which can have an effect favorable to cell performance such as rapid charging.

[0035] The weight ratio of the silicon-based active material and the first carbon-based active material included in the first cathode composite layer (21) may be 1:5 to 20, and specifically 1:7 to 17. Within this range, the rapid charging characteristics and room temperature life characteristics of the battery can be improved, while the deterioration of high temperature life characteristics can be suppressed.

[0036] The second cathode composite layer (22) comprises a magnesium-doped silicon-based active material and a second carbon-based active material.

[0037] The silicon-based active material of the second cathode composite layer (22) is SiO x(0 <x<2)을 포함할 수 있다. 일반적으로 상기 x 값이 작을수록 전지 용량이 증가하며 전지 수명이 저하되고, 상기 x 값이 클수록 전지 용량이 저하되어 전극의 에너지 밀도가 낮아지는 문제가 있다. 따라서, 본 발명에서는 상기 x를 상기 범위로 제공하여 전지의 용량을 확보하면서 에너지 밀도를 확보할 수 있다.

[0038] The silicon-based active material may further include a carbon coating layer formed on the particles. Accordingly, the silicon-based active material particles can be prevented from coming into contact with moisture in the atmosphere and / or water in the negative electrode slurry. Thus, the reduction in the discharge capacity of the secondary battery can be suppressed.

[0039] For example, the carbon coating layer may be at least one selected from the group consisting of amorphous carbon, carbon nanotubes, carbon nanofibers, graphite, graphene, graphene oxide, and reduced graphene oxide.

[0040] At least one of the silicon-based active material of the first cathode composite layer (21) and the silicon-based active material of the second cathode composite layer (22) may have a carbon coating layer disposed on the outermost portion.

[0041] The silicon-based active material may include magnesium doping, and the magnesium-doped silicon-based active material may include micropores. Accordingly, swelling of the silicon-based active material during charging and discharging may be reduced, thereby suppressing cracking of the active material containing silicon oxide during charging and discharging, which can improve the rapid charging life characteristics and cycle characteristics at room temperature of the lithium secondary battery, but high-temperature life characteristics may be degraded due to irreversible side reactions.

[0042] In this regard, the present invention places a first negative electrode composite layer (21) containing a silicon-based active material that is not doped with magnesium and includes a porous structure in the lower layer, and a second negative electrode composite layer (22) containing a silicon-based active material that is doped with magnesium in the upper layer. By doing so, the silicon-based active material containing a porous structure located in the lower layer can mitigate the occurrence of electrode cracks caused by volume expansion of the magnesium-doped silicon-based active material located in the upper layer and maintain conductivity, thereby preventing the deformation of the electrode structure. Additionally, the magnesium-doped silicon-based active material located in the upper layer can simultaneously provide the effect of improving not only general lifespan characteristics but also rapid charging lifespan characteristics and cycle characteristics at room temperature.

[0043] The silicon-based active material can be formed by mixing, heating, cooling, and grinding the silicon-based active material and the magnesium source. The magnesium source may be solid magnesium. Additionally, a mixture can be formed by mixing the silicon-based active material and the magnesium source.

[0044] The content of the magnesium source relative to the total weight of the above mixture may be 5 to 17 weight percent. Within this range, a sufficient amount of magnesium is doped into the silicon-based active material, while preventing the silicon content from being excessively reduced, thereby preventing the degradation of the capacity characteristics of the secondary battery.

[0045] The Mg1s spectrum of the surface of a magnesium-doped silicon-based active material measured by X-ray photoelectron spectroscopy (XPS) can satisfy Equation 1 below.

[0046] [Equation 1]

[0047] P Mg / (P Mg +P MgO )≤0.6

[0048] In Equation 1, P Mgis the area of ​​the 1303 eV peak of the above Mg1s spectrum, and P MgO is the area of ​​the 1304.5 eV peak of the above Mg1s spectrum.

[0049] The above P Mg is the area of ​​the peak (1303 eV) representing the element magnesium, and P MgO is the area of ​​the peak (1304.5 eV) representing the bonding of magnesium and oxygen elements.

[0050] For example, P in Equation 1 Mg / (P Mg +P MgO The value can represent the proportion of magnesium metal among the magnesium metal, magnesium oxide, and magnesium hydroxide present on the surface of the magnesium-doped silicon-based active material.

[0051] In the XPS spectrum satisfying Equation 1 above, magnesium remaining on the surface of the magnesium-doped silicon-based active material can be converted into magnesium hydroxide, thereby suppressing side reactions. Accordingly, the degradation of the lifespan characteristics of the lithium secondary battery can be prevented.

[0052] The above mixture may be calcined at a temperature of 1000 to 1800 ℃ and then cooled to precipitate a silicon oxide composite containing magnesium. The silicon oxide composite containing magnesium may be ground and classified to form a silicon-based active material doped with magnesium.

[0053] The weight ratio of the silicon-based active material and the second carbon-based active material included in the second cathode composite layer (22) may be 1:4 to 16, and specifically 1:7 to 12. Within this range, the rapid charging characteristics and room temperature life characteristics of the battery can be improved, while the deterioration of high temperature life characteristics can be suppressed.

[0054] The silicon-based active material containing the porous structure may be doped with a metal other than magnesium. The silicon-based active material containing the porous structure may be doped with at least one metal selected from the group consisting of Li, Al, Ca, Fe, Ti, and V. Accordingly, the conductivity and / or structural stability of the silicon-based active material containing the porous structure may be improved.

[0055] For example, when using only natural graphite as the negative electrode active material, the adhesion to the negative electrode current collector is excellent, but resistance increases during rapid charging and discharging, which may degrade output characteristics. Additionally, the natural graphite may be damaged due to the expansion of the silicon-based active material, which can reduce the mobility of lithium ions. Consequently, side reactions at the negative electrode and a decrease in lifespan characteristics may occur.

[0056] The first carbon-based active material and the second carbon-based active material may each be one selected from natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, amorphous carbon fine powder, coke powder, meso-phase carbon, vapor-phase grown carbon fiber, pitch-based carbon fiber, polyacrylonitrile-based carbon fiber, and combinations thereof, and may also be sucrose, phenolic resin, naphthalene resin, polyvinyl alcohol, furfuryl alcohol resin, polyacrylonitrile resin, polyamide resin, furan resin, cellulose resin, styrene resin, polyimide resin, epoxy resin, vinyl chloride resin, citric acid, thiaric acid, polyfluorovinylidene, carboxymethylcellulose (CMC), hydroxypropylcellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, and ethylene-propylene-diene. It may be obtained by carbonizing precursors of monomer (EPDM), sulfonated EPDM, starch, glucose, gelatin, sugars, coal-based pitch, petroleum-based pitch, polyvinyl chloride, mesophase pitch, tar, low molecular weight heavy oil, and combinations thereof, and specifically may include artificial graphite and / or natural graphite. Accordingly, the adhesion between the negative electrode current collector (10) and the negative electrode composite layer (20) and the output characteristics of the secondary battery can be improved together.

[0057] The first carbon-based active material and the second carbon-based active material may include the same carbon-based active material or different carbon-based active materials.

[0058] The first cathode composite layer (21) can be formed by applying, drying, and rolling a silicon-based active material and a first carbon-based active material containing a porous structure onto a cathode current collector (10).

[0059] The second cathode composite layer (22) above can be formed by applying, drying, and rolling a silicon-based active material coated with magnesium and a second carbon-based active material onto a cathode current collector (10).

[0060] The first cathode composite layer (21) may be a mixture of a silicon-based active material and a first carbon-based active material including a porous structure, as well as a cathode binder, a conductive material and / or a dispersant.

[0061] The second cathode composite layer (22) may be a mixture of a silicon-based active material coated with magnesium and a second carbon-based active material, as well as a cathode binder, a conductive material and / or a dispersant.

[0062] The above binder is a compound that serves to adhere the components within the cathode composite layer (20) well to each other and to adhere the cathode composite layer (20) well to the current collector, and may be at least one rubber-based binder selected from the group consisting of styrene-butadiene rubber (SBR), fluoropolymer, ethylene propylene rubber, butyl acrylate rubber, butadiene rubber, isoprene rubber, acrylonitrile rubber, acrylic rubber and silane rubber; a cellulose-based binder such as carboxymethylcellulose (CMC), hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof; a water-soluble polymer-based binder such as a polyacrylic acid (PAA)-based binder, a polyvinyl alcohol (PVA)-based binder, and a polyvinyl alcohol-polyacrylic acid copolymer (PVA-PAA Copolymer)-based binder; and a combination thereof. Specifically, the first cathode composite layer and the second cathode composite layer may each further include a rubber-based binder. More specifically, the first cathode composite layer (21) and the second cathode composite layer (22) may independently further include a rubber-based binder and a cellulose-based binder.

[0063] The above conductive material is used to impart conductivity to the electrode and maintain the structure of the electrode, and may be used as a conductive material that does not cause adverse reactions with other elements of the secondary battery. Examples include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, or silver; conductive whiskey such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one of these alone or a mixture of two or more may be used. Specifically, the above conductive material may include carbon nanotubes (CNT). Compared to conventional conductive materials such as carbon black, carbon nanotubes (CNT) have a higher electron mobility, enabling the realization of high energy density with a small amount; possess high strength due to their stable structure; and can substantially mitigate the volume expansion of silicon-based active materials. Therefore, if the above conductive material includes carbon nanotubes (CNT), the energy density, lifespan characteristics, and resistance characteristics of the electrode may be even better.

[0064] As the above-mentioned dispersant, a CMC-based dispersant can be used as a carbon nanotube dispersant.

[0065] Preparation Example

[0066] (1) Preparation of the cathode

[0067] 1) Preparation of the first cathode composite layer

[0068] A first cathode composite layer composition in the form of a slurry was prepared by adding water to 80.05 wt% of artificial graphite (D50: 20 μm) as a carbon-based active material, 16.00 wt% of SiC as a silicon-based active material containing a porous structure, 0.25 wt% of SWCNT conductive material, and 3.7 wt% of CMC / SBR (binder, 1.30 / 2.40 weight ratio).

[0069] 2) Preparation of magnesium-doped silicon-based active material

[0070] Silicon oxide (SiO₂) as a silicon-based active material x , 0 <x<2, D50: 6 ㎛)에, 실리콘계 활물질의 총 중량 대비 8 중량%에 해당하는 양의 마그네슘을 투입 및 혼합하여 마그네슘이 도핑 된 실리콘계 활물질을 제조하였다.

[0071] Specifically, silicon and SiO2 were mixed in a 1:1 ratio, and 8% by weight of magnesium relative to the total weight of the magnesium-doped silicon-based active material was mixed with silicon and SiO2 to form a mixture.

[0072] The above mixture was calcined at a temperature of 1500°C and then cooled to precipitate a silicon oxide composite containing magnesium. The precipitated silicon oxide composite was ground and classified to produce a magnesium-doped silicon-based active material.

[0073] 3) Preparation of the second cathode composite layer

[0074] A second cathode composite layer composition in the form of a slurry was prepared by adding water to a solid component comprising 80.05 wt% of artificial graphite (D50: 20 μm) as a carbon-based active material, 16.00 wt% of the magnesium-doped silicon-based active material prepared above, 0.25 wt% of SWCNT conductive material, and 3.7 wt% of CMC / SBR (binder, 1.30 / 2.40 weight ratio).

[0075] (2) Manufacturing of lithium secondary batteries

[0076] A cathode was manufactured by applying the first cathode composite layer and the second cathode composite layer prepared above differently as shown in Table 1 below.

[0077] Li[Ni as a positive electrode active material 0.88 Co 0.1 Mn 0.02A slurry was prepared by mixing O2, MWCNT as a conductive material, and polyvinylidene fluoride (PVdF) as a binder in a weight ratio of 98.08:0.72:1.2. The slurry was uniformly coated onto an aluminum foil 12 μm thick and vacuum dried to produce a cathode for a secondary battery. At this time, about 20 wt% of the MWCNT content consisted of a CNT dispersant.

[0078] An anode and a cathode were each notched to a predetermined size and laminated, and a separator (polyethylene, thickness 13 μm) was interposed between the anode and the cathode to form an electrode cell, after which the tab portions of the anode and the cathode were welded. The welded assembly of the anode / separator / cathode was placed inside a pouch, and three sides were sealed, excluding the surface for electrolyte injection. At this time, the portion containing the electrode tabs was included in the sealed portion.

[0079] Electrolyte was injected through the remaining surface excluding the sealing part, and after sealing the remaining surface, it was impregnated for at least 12 hours.

[0080] The electrolyte used was prepared by dissolving 1.1M LiPF6 in a mixed solvent of EC / EMC (25 / 75; volume ratio) and then adding 8 wt% fluoroethylene carbonate (FEC), 0.5 wt% 1,3-propensulfon (PRS), and 1.0 wt% 1,3-propanesulfon (PS).

[0081] Subsequently, Heat Press Precharging was performed for 60 minutes with a current corresponding to an average of 0.5C. After stabilization for more than 12 hours, degassing was performed, and after aging for more than 24 hours, formation charge and discharge were carried out (charging conditions CC-CV 0.25C 4.2V 0.05CCUT-OFF, discharging conditions CC 0.25C 2.5V CUTOFF).

[0082] Afterwards, standard charging and discharging were performed (charging conditions CC-CV 0.33 C 4.2V 0.05C CUT-OFF, discharging conditions CC 0.33C 2.5V CUT-OFF).

[0083] cathode structure Upper and lower layer thickness ratio Examples Upper layer: Second cathode composite layer 1 Lower layer: First cathode composite layer 1 Comparative Example 1 Upper layer: First cathode composite layer 1 Lower layer: Second cathode composite layer 1 Comparative Example 2 First cathode composite layer alone - Comparative Example 3 Second cathode composite layer alone -

[0084] Evaluation Example: Evaluation of rapid charging life characteristics and evaluation of general (room temperature) life characteristics

[0085] (1) Rapid charging life performance evaluation

[0086] A lithium secondary battery prepared according to Examples and Comparative Examples 1 to 3 was charged to reach DOD72 within 35 minutes using a step charging method at a C-rate of 3.25C / 3.0C / 2.75C / 2.5C / 2.25C / 2.0C / 1.75C / 1.5C / 1.25C / 1.0C / 0.75C / 0.5C, and then discharged at 1 / 3C. A rapid charging evaluation was conducted by repeating the cycles, with the above charging and discharging being one cycle. After repeating 300 cycles with a 10-minute waiting time between charge and discharge cycles, the rapid charging capacity retention rate was measured.

[0087] (2) General (room temperature) lifespan performance evaluation

[0088] Lithium secondary batteries prepared according to Examples and Comparative Examples 1 to 3 were evaluated for general charge life characteristics in the DOD94 (SOC4-98) range in a chamber maintained at 25°C. Under constant current / constant voltage (CC / CV) conditions, the battery was charged at 0.3C to a voltage corresponding to SOC98 and then cut off at 0.05C. Subsequently, the battery was discharged at 0.3C to a voltage corresponding to SOC4 under constant current (CC) conditions, and the discharge capacity was measured. After repeating this for 500 cycles, the discharge capacity retention rate for general (room temperature) life characteristics evaluation was measured.

[0089] (3) Energy density measurement

[0090] Wh / L measurements can usually be obtained directly from charge / discharge data and can be calculated by dividing the capacity (Ah) x average voltage (v) by the cell volume.

[0091] Fast Charge Life Capacity Retention Rate (300 Cycles, %) Room temperature lifetime capacity retention rate (300 cycles, %) Energy density (Wh / L) Examples 84 97.0 775 Comparative Example 1 88.8% @ 200cyc followed by a sharp decline 97.0 775 Comparative Example 2 94.4% @ 100cyc followed by a sharp drop 97.2 775 Comparative Example 3 82.1 96.2 775

[0092] According to Table 2 above, the lithium secondary battery of the embodiment containing a first cathode composite layer in the lower layer and a second cathode composite layer in the upper layer exhibited improved rapid charging life characteristics and general life characteristics compared to the comparative examples.

[0093] Specifically, it can be seen that when the same cathode composite layer as in the example is used but the upper and lower layers are reversed (Comparative Example 1), the rapid charging life drops sharply after 200 cycles.

[0094] In addition, it can be seen that when the magnesium-doped cathode composite layer is not included (Comparative Example 2), the rapid charging life drops sharply after 100 cycles.

[0095] Furthermore, when a magnesium-doped cathode composite layer is used but does not include a multilayer cathode composite layer (Comparative Example 3), it can be confirmed that the metal charge life characteristics and general life characteristics are degraded compared to the secondary battery of the example.

[0096] Although representative embodiments of the present invention have been described in detail above, those skilled in the art will understand that various modifications can be made to the above-described embodiments without departing from the scope of the present invention. Therefore, the scope of the present invention should not be limited to the described embodiments, but should be defined by the claims set forth below as well as equivalents thereof. Explanation of the symbols

[0097] 100: Negative electrode for lithium secondary battery 10: Cathode current collector 20: Cathode composite layer 21: First cathode composite layer 22: Second cathode composite layer

Claims

Claim 1 A negative electrode current collector; a first negative electrode composite layer formed on at least one surface of the negative electrode current collector and comprising a silicon-based active material including a Si-C composite, a first carbon-based active material, a conductive material, and a binder; and a magnesium-doped SiOx(0) formed on the first negative electrode composite layer. <x<2) 실리콘계 활물질,제2 탄소계 활물질, 도전재 및 바인더를 포함하는 제2 음극 합제층;을 포함하는, 리튬 이차 전지용 음극. Claim 2 A negative electrode for a lithium secondary battery according to claim 1, wherein the Si-C composite comprises carbon-based particles containing pores and a silicon-containing coating formed inside the pores of the carbon-based particles or on the surface of the carbon-based particles. Claim 3 A negative electrode for a lithium secondary battery according to claim 1, wherein the binders of the first negative electrode composite layer and the second negative electrode composite layer comprise a rubber-based binder and a cellulose-based binder. Claim 4 A negative electrode for a lithium secondary battery according to claim 1, wherein the conductive material of the first negative electrode composite layer and the second negative electrode composite layer comprises one or more selected from the group consisting of carbon nanotubes (CNT) and graphite. Claim 5 A negative electrode for a lithium secondary battery according to claim 1, wherein the first carbon-based active material and the second carbon-based active material are independently one or more selected from the group consisting of natural graphite, artificial graphite, graphitized carbon fiber, graphitized mesocarbon microbeads, and amorphous carbon. Claim 6 A negative electrode for a lithium secondary battery according to claim 1, wherein the weight ratio of the silicon-based active material and the first carbon-based active material included in the first negative electrode composite layer is 1:5 to 20. Claim 7 A negative electrode for a lithium secondary battery according to claim 1, wherein the weight ratio of the silicon-based active material and the second carbon-based active material included in the second negative electrode composite layer is 1:4 to 16. Claim 8 A negative electrode for a lithium secondary battery according to claim 1, wherein the thickness ratio of the first negative electrode composite layer and the second negative electrode composite layer is 1:1 to 1.

25. Claim 9 A negative electrode for a lithium secondary battery according to claim 1, wherein at least one of the silicon-based active material of the first negative electrode composite layer and the silicon-based active material of the second negative electrode composite layer has a carbon coating layer disposed on the outermost portion. Claim 10 A lithium secondary battery comprising a negative electrode of any one of claims 1 to 9; and a positive electrode disposed opposite to the negative electrode.

Citation Information

Patent Citations

  • Silicon-based composite, negative electrode and lithium secondary battery comprising the same

    KR1020200023240A

  • Lithium secondary battery

    KR1020210096814A

  • Cathode active material for lithium secondary battery

    KR1020220073074A

  • Anode for secondary battery and lithium secondary battery including the same

    KR1020220114249A